ChemInform Abstract: Mutual Cooperation in the Formal Allyl Alcohol Nucleophilic Substitution and Hydration of Alkynes for the Construction of γ‐Substituted Ketones. Issue 39 (September 2016) - Huang, Kaimeng; Wang, Hongkai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: The mild one‐pot reaction between aryl substituted 3‐hydroxy‐1‐en‐5‐ynes and a broad range of O, C or N‐nucleophiles delivers ketones in generally high yields.